An Isolable Bis(Germylene)‐Stabilized Plumbylone. (14th December 2022) - Chen, Ming; Zhang, Zhaoyin; Qiao, Zihao; Zhao, Lili; Mo, Zhenbo
Abstract: We report herein the synthesis of a stable plumbylone (3 ) by reduction of a bromodigermylplumbylene (2 ) with 2.2 equiv of potassium graphite (KC8 ). The molecular structure of 3 was established by a single‐crystal X‐ray diffraction study and features a two‐coordinated Pb center with an acute Ge−Pb−Ge bond angle. Computational studies showed that this complex (3 ) possesses a singlet electronic ground state with a Pb 0 center. Its high thermal stability can be most likely ascribed to the delocalization of π electrons over the Ge−Pb−Ge moiety. A preliminary reactivity study demonstrates that complex 3 can deliver Pb 0 atoms to an organic azide producing a tetrameric imido complex [(PbNDipp)4 ] (Dipp=2, 6‐ i Pr‐C6 H3, 4 ) and perform a metathesis reaction with GeCl2 ⋅dioxane to produce a bis(germylene)‐stabilized germylone (5 ), highlighting the synthetic utility of 3 . Abstract : A stable plumbylone was synthesized and characterized, which possesses a singlet electronic ground state with a Pb 0 center. In accord with its electron‐rich nature, the plumbylone exhibits intriguing reactivity involving transfer of Pb 0 atom to an organic azide to form a tetrameric imido complex and undergoing a metathetic reaction with GeCl2 ⋅ dioxane to afford a germylone.